Elasticity of Substitution and the Retardation of Soviet Growth Rates - Blitzer, Charles R. (The Review of Economics and Statistics, 1970)
In a recent issue of this journal, Professor Norman Kaplan discusses the retardation in the rate of growth of output in the Soviet Union during the last decade. Assuming a Cobb-Douglas production function he concludes that is established independently of the capital share that the rate of increase of factor productivity for industry declines between 1951-1958 and 1958-1963. In his model this conclusion holds not only for industry, but for every other sector as well and for the economy as a whole. In using the Cobb-Douglas function, Kaplan implicitly assumes that the elasticity of substitution between the factors of production is unity. There is some evidence, however, that the elasticity of substitution is less than unity in many Western countries and a recent study by Weitzman [8] suggests a similar result for the Soviet Union. It is the purpose of this paper to examine the sensitivity of Kaplan's results to variations in the elasticity of substitution. In the model I propose, bounds will be derived on the elasticity of substitution consistent with either of two extreme assumptions concerning the cause of the retardation in output growth. These assumptions are that the decline is entirely due to a decline in technological progress or that the decline is entirely due to a decline in the rate of growth of combined factor inputs. It is not my purpose to get very involved in the question of data reliability or consistency. Rather, I take as a point of departure the data recently compiled in Kaplan [4] which I believe are relatively reliable. His results for output are presented in table 1. For national and nonagricultural product and for each sector except services, the average annual rate of growth in 1958-1963 evidently is less than in 1950-1958 or 1953-1958. Comparing the periods 1953-1958 and 1958-1963, we find the average annual rate of output increase declined 30 per cent i-n industry, 25 per cent in transport and communications, and 46 per cent in construction. This retardation assumes more significance when it is noted that these are the very sectors the Soviets have counted on to lead their economic development.